Metode Mengajar Pendidikan Islam Dalam Kisah Luqman Al-Hakim - Rohadi Rohadi (THE JOER: Journal Of Education Research, 2022)
Al-Qur’an is a plenary and perfect holy book that contains a number of the past stories about human being that can be used as a learning (i’tibar) for the human in future. One of the stories in al-Qur’an that has a high value is the story of Luqman al-hakim. It tells about the advice of Luqman al-Hakim towards his children as stated in al-Qur’an in the letter of Luqman sentences of 12-19. The aim of this research is to (a) analyze the story of Luqman al-Hakim, (b) observe the material of Islamic education embedded in the story of Luqman al-Hakim ad (c) observe the method of Islamic education given by Luqman al-Hakim. The method applied in this research is a qualitative method by interpreting the texts of al-Qur’an sentences called the method of thematic interpretation. Meanwhile, the data analysis is conducted using content analysis and the descriptive-interpretative model. The conclusion of the research results shows that the education method used by Luqman al-Hakim can be considered as (1) method of advising, (2) method of understanding and (3) method of implementing.